2009
DOI: 10.1111/j.1365-2265.2008.03391.x
|View full text |Cite
|
Sign up to set email alerts
|

GH replacement in patients with non‐functioning pituitary adenoma (NFA) treated solely by surgery is not associated with increased risk of tumour recurrence

Abstract: GH replacement in patients with NFA treated by surgery alone is not associated with an increased risk of tumour recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…Additional characteristics of the included studies are shown in Table 1. As shown in table, seven of the selected studies obtained seven or more scores, which indicated that the study quality was relatively higher [5][6][7][14][15][16][17][18][19][20][21][22]; whereas, other studies with relatively lesser scores were considered of lower quality [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional characteristics of the included studies are shown in Table 1. As shown in table, seven of the selected studies obtained seven or more scores, which indicated that the study quality was relatively higher [5][6][7][14][15][16][17][18][19][20][21][22]; whereas, other studies with relatively lesser scores were considered of lower quality [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…However, the results from intracranial tumors treated with GH indicated that GHRT was not associated with increased risk of recurrence/progression. During the period of GH treatment, the dose of GH was adjusted regularly depending on serum level of IGF-1 [5]. Thus, in patients treated with GH, the level of GH was elevated in accordance with the normal reference levels of IGF-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary neoplasias were detected both before and after commencing GH replacement (67). Finally, in 130 patients with non-functioning pituitary adenoma treated with surgery alone, treatment with GH for a mean period of 6.8 years was not associated with increased recurrence of the pituitary tumour (68). Therefore, these relatively small studies do not suggest that GH replacement increases the recurrence or regrowth of hypothalamicpituitary tumours.…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 84%